Empirical charging behavior of plug-in hybrid electric vehicles. (1st September 2022) - Mandev, Ahmet; Plötz, Patrick; Sprei, Frances; Tal, Gil
Highlights: We analyze over 10, 000 PHEV with a total of 4.3 million driving days. We propose a new method to detect the frequency of individual charging behavior. Users avoid high share of nights without charging. Not charging overnight has a large effect on the share of electric driving. Intense drivers have high electric km per year with low shares of electric driving. Abstract: Plug-in hybrid electric vehicles (PHEV) offer greenhouse gas emission reduction in car usage if charged frequently and driven mainly on electricity. However, little is known about the actual charging behavior of PHEV owners. Here, we investigate the daily charging of 10, 488 Chevrolet Volt PHEV driven on a total of 4.3 million total driving days in the US and Canada. We propose a new method to detect the frequency of individual charging behavior from the daily utility factor and daily distance travelled. Our results show that no charging overnight occurs typically on 3–7% of the driving days per user and additional charging happens on 20–26% of the driving days. We also analyze the relation between charging frequency and utility factor for different user groups and days. Our results show that the utility factor should not be used as the only measure of environmental performance of PHEVs.